Pengaruh Gaya Hidup dan Trend Fashion terhadap Keputusan Pembelian Konsumen Ta Butik Kendal - Putri, Ikhsti Marwinda; Irmadiani, Nadia Dwi (Business Perspective Journal, 2024)
As time progress, certain fashion trends that were previously only seen from clothing styles have evolved and developed into lifestyle entities, which are driven by the easy exchange of information and external references. Lifestyle and fashion trends are only to fulfill self-satisfaction. Especially Generation Z often buy goods without prioritizing their needs or just to show off on social media to be recognized by others. The aim of this research is to determine whether there is an influence of lifestyle and fashion trends on Generation Z purchasing decisions among TA Boutiques Kendal consumers. The data used in this research were 96 respondents aged 16-27 years and the sampling technique used purposive sampling technique. Hypothesis testing uses validity, reliability, multiple linear and correlation tests using SPSS 25 software. The research results show that lifestyle has a positive and significant influence on purchasing decisions, fashion trends have a positive and significant influence on purchasing decisions, there is a joint influence between lifestyle and fashion trends on purchasing decisions. Keywords: lifestyle, fashion trends, purchasing decisions